2021
DOI: 10.3847/1538-4357/ac04b5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Model of the Milky Way Using APOGEE and Gaia Data

Abstract: We construct a dynamical model of the Milky Way disk from a data set that combines Gaia EDR3 and APOGEE data throughout galactocentric radii in the range 5.0 kpc ≤ R ≤ 19.5 kpc. We make use of the spherically aligned Jeans anisotropic method to model the stellar velocities and their velocity dispersions. Building upon our previous work, our model is now fitted to kinematic maps that have been extended to larger galactocentric radii due to the expansion of our data set, probing the outer regions of the Galactic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 104 publications
2
14
0
Order By: Relevance
“…This theoretical expectation was confirmed by recent Gaia studies which found that the velocity ellipsoid is well approximated by an alignment with the spherical polar coordinate system, both in the outer stellar halo (Wegg et al 2019) and in the disk region (Hagen et al 2019;Everall et al 2019). These data motivates the development of a practically-usable spherically-aligned solution for the Jeans equations, which we already successfully applied to the Gaia data (Nitschai et al 2019).…”
Section: Motivationsupporting
confidence: 72%
See 1 more Smart Citation
“…This theoretical expectation was confirmed by recent Gaia studies which found that the velocity ellipsoid is well approximated by an alignment with the spherical polar coordinate system, both in the outer stellar halo (Wegg et al 2019) and in the disk region (Hagen et al 2019;Everall et al 2019). These data motivates the development of a practically-usable spherically-aligned solution for the Jeans equations, which we already successfully applied to the Gaia data (Nitschai et al 2019).…”
Section: Motivationsupporting
confidence: 72%
“…This method has already been applied to model the Gaia DR2 data, where we found it describes the observations remarkably well with minimal freedom and good accuracy (Nitschai et al 2019). I leave further applications to real data to future studies.…”
Section: Discussionmentioning
confidence: 79%
“…We integrate stellar orbits for different SSPs(τ) using the galpy 3 package subject to the MWPotential2014 gravitational potential (Bovy 2015). For the rotational velocity v T at the so-3 http://github.com/jobovy/galpy lar distance R we use the one computed by Ablimit et al (2020) applying the three-dimensional velocity vector method for Cepheids (v T = 232.5 ± 0.83 km s −1 ) that is consistent with the most recent estimation by Nitschai et al (2021) with a dynamical model of the Milky Way using APOGEE and Gaia data. The initial vertical velocity for the SSP v 0,z (τ) born at the evolutionary time t B = t G − τ has been chosen by satisfying the following condition:…”
Section: Computing the Orbital Maximum Vertical Excursion And The Ver...supporting
confidence: 64%
“…We find V circ,0 ≡ r 0 0 ≈ 241 km s −1 . This value of the circular velocity is just slightly greater than the values V circ,0 ≈ 233 km s −1 , V circ,0 ≈ 229 km s −1 , V circ,0 ≈ 234 km s −1 , V circ,0 ≈ 239 km s −1 , and V circ,0 ≈ 235 km s −1 measured by McMillan (2017), Eilers et al (2020), Mróz et al (2019), VERA Collaboration (2020), and Nitschai et al (2021), respectively, adopting the fundamental axisymmetric model.…”
Section: R E S U Lt S O F C a L C U L At I O Nmentioning
confidence: 60%